Evaluation of the impact of the leached and solubilized extracts on the germination of cabbage seeds (Brassica oleracea var. capitata) - Thode Filho, Sérgio; Souza, Leonardo Corrêa de; Jorge, Emanuele Nunes de Lima Figueiredo; Sena, Marcelo Fonseca Monteiro de; Franco, Heider Alves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
The germination and seedling root development trials have been used to evaluate and quantify the toxicity of water-soluble compounds as well as mixtures of complex substances, leached, among others. The objective was to evaluate the impact of leached and solubilized extracts of coffee waste on the germination and development of cabbage seedlings (B. oleracea var. Capitata), as well as to evaluate the physical and chemical properties of these extracts. The extracts were prepared according to the Brazilian Association of Technical Standards 10.005 and 10.006, respectively. The experimental design had 7 treatments for the test group (leached), 7 treatments for the test group (solubilized) and one control group. The control group was composed of 4 mL distilled water. It was verified that from the lowest dosage administered (0.1 mL) there was an inhibition in the germination of 30% for both extracts. Starting the dose with 0.7 mL of leached, no root growth was observed. The determination of LOEC was established in the treatments with 0.1 mL for both extracts.